Ekstrak Daun Salam (Syzgium Polyantha L) Dengan Metode Soxhlet Sebagai Inhibitor Korosi Pada Baja Karbon ASTM A36 Dalam Media Korosi NAOH Dan HCL - Oding Sitorus; Komalasari Komalasari; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Corrosion is defined as the result of damage from a chemical reaction between a metal and its environment. The use of inhibitors is one way to inhibit the corrosion rate. Bay leaf extract is an organic material that can be used as an inhibitor. The purpose of this study was to determine the effect of adding bay leaf extract on the corrosion rate of ASTM A36 carbon steel in 0.5 M HCL and 1 M NaOH corrosive media. The extraction method used was socletation with a ratio of ethanol : distilled water 1: 3 and immersion time of 24 hours, 36 hours, 48 hours and 60 hours. The effectiveness of using bay leaf inhibitors (0 and 2.5 gr/L) is known through the weight loss test. FTIR test results show that the bay leaf extract contains tannin compounds which can inhibit the corrosion rate that occurs in ASTM A36 carbon steel when used as a corrosion inhibitor. The best efficiency occurred at a concentration of 2.5 g / L with a soaking time for 60 hours in a 0.5 M HCL solution of 82%. Keywords: bay leaf extract, carbon steel, corrosion rate, inhibitor efficiency